2020
DOI: 10.1093/gbe/evaa239
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Epigenetic Signatures of Adaptive Developmental Plasticity in the Andes

Abstract: High-altitude adaptation is a classic example of natural selection operating on the human genome. Physiological and genetic adaptations have been documented in populations with a history of living at high altitude. However, the role of epigenetic gene regulation, including DNA methylation, in high-altitude adaptation is not well understood. We performed an epigenome-wide DNA methylation association study based on whole blood from 113 Peruvian Quechua with differential lifetime exposures to high altitude (&… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 118 publications
1
13
0
Order By: Relevance
“…In a new study in Genome Biology and Evolution titled “Genome-Wide Epigenetic Signatures of Adaptive Developmental Plasticity in the Andes,” Ainash Childebayeva, a doctoral student at the University of Michigan at the time of the study, and her colleagues sought to answer this question by studying members of the Peruvian Quechua, who live at high altitudes in the Andes. Their work reveals that mechanisms like DNA methylation may be involved in adaptation to high altitudes, and their findings have potential implications for the long-term health of those living at such heights ( Childebayeva et al. 2021 ).…”
mentioning
confidence: 99%
“…In a new study in Genome Biology and Evolution titled “Genome-Wide Epigenetic Signatures of Adaptive Developmental Plasticity in the Andes,” Ainash Childebayeva, a doctoral student at the University of Michigan at the time of the study, and her colleagues sought to answer this question by studying members of the Peruvian Quechua, who live at high altitudes in the Andes. Their work reveals that mechanisms like DNA methylation may be involved in adaptation to high altitudes, and their findings have potential implications for the long-term health of those living at such heights ( Childebayeva et al. 2021 ).…”
mentioning
confidence: 99%
“…We found CLK2 methylation to be positively associated with SaO 2 , suggesting that CLK2 expression is potentially decreased in hypoxic conditions, given methylation is linked to gene repression. Interestingly, the CpG site in CLK2 is upstream of the gene PKLR that is significantly differentially methylated in high- compared to low-altitude Quechua ( Childebayeva et al, 2020 ). We also found a CpG site upstream of TOR4A (Torsin family 4 member A), which is associated with dystonia ( Cascalho et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…DNA methylation patterns can change upon exposure to various environmental conditions, including exposure to different diets, stress, and toxicants ( Dolinoy et al, 2007 ; Baccarelli et al, 2009 ; Colacino et al, 2012 ; Childebayeva et al, 2019b ). Previous studies have demonstrated that changes in DNA methylation are associated with exposure to the low oxygen environment of high altitude ( Alkorta-Aranburu et al, 2012 ; Childebayeva et al, 2019a , b , 2020 ). These studies show that genes in the hypoxia inducible factor (HIF) pathway exhibit changes in DNA methylation associated with high-altitude exposure.…”
Section: Introductionmentioning
confidence: 99%
“…In vitro experiments with human fibroblasts showed that the progression of DNAmAge was slower under hypoxia (1% oxygen) compared to normoxia (21% oxygen) [72]. On the contrary, in humans, high-altitude exposure was found to accelerate aging as predicted using epigenetic clocks [73].…”
Section: Epigenetic Adaptation Of Animals To High Altitudementioning
confidence: 99%
“…For example, differences in the DNA methylation pattern among major ethnic groups has been observed [77]. Genome-wide DNA methylation studies in high-altitude adaptation is a great technique which will help in determining the individual genes and pathways that may undergo changes in DNA methylation in association with adaptation to highaltitude [73,78]. Epigenome-wide DNA methylation association study based on whole blood from 113 Peruvian Quechua with differential lifetime exposures to high-altitude (>2500 m) showed two significant differentially methylated positions (DMPs) and 62 differentially methylated regions (DMRs) associated with high-altitude developmental and lifelong exposure statuses.…”
Section: Epigenetic Adaptation Of Animals To High Altitudementioning
confidence: 99%